NATIVE SPECIES FOR DEGRADED PEAT SWAMP FOREST REHABILITATION - Hesti L Tata; Sukaesih Pradjadinata (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
It is known that over exploitation and repeated fire caused peat swamp forest degradation. Great effort on degraded peat forest rehabilitation has been taken to minimize forest degradation. The study aimed to understand the best tree species for degraded peat swamp forest rehabilitation. The study was conducted on degraded and burnt peat swamp forest of Tumbang Nusa Forest Research area, Central Kalimantan. The study was designed in a completely randomized design, using four native species, viz. Shorea balangeran, Dyera poyphylla, Calophyllum bifflorum, and Callophyllum inophyllum. The seedlings were planted in planting space of 5 m x 2.5 m. After eight months planting, S. balangeran had the highest seedlings survival. Environmental factors, such as ground water table and precipitation, in the demo-plot are presented.Key words: reforestation, degraded peatland, peat fire, Central Kalimantan